Discovery of the first early Cenozoic euprimate (Mammalia) from Inner Mongolia - Ni, Xijun.; Beard, K. Christopher.; Meng, Jin (Paleontologist); Wang, Yuan-qing.; Gebo, Daniel Lee, 1955- (New York, NY : American Museum of Natural History, 2007)
11 p. : ill. 26 cm. Includes bibliographical references (p. 10-11). Although it is widely thought that euprimates originated in Asia, the fossil record of early euprimates remains sparse there. We describe herein a new omomyid euprimate, Baataromomys ulaanus, n. gen. et sp., based on an isolated right lower m2 from Bumbanian strata at Wulanboerhe in the Erlian Basin of Inner Mongolia, China. In terms of the size and proportions of m2, Baataromomys ulaanus is intermediate between Eurasian and North American species that are usually assigned to Teilhardina. Morphologically, m2 of Baataromomys differs from that of Teilhardina and North American small-bodied omomyids (including Anemorhysis, Tetonoides, Trogolemur, and Sphacorhysis) in having a smaller paraconid that is less fully connate with the metaconid, a lower entoconid, a weaker crest connecting the metaconid with the entoconid, and a weaker buccal cingulid. The new taxon is much smaller and lower crowned than Steinius, a genus commonly regarded as a basal omomyid. Despite the substantial difference in size, the m2s of Baataromomys and Steinius share some important features, including a very broad talonid basin and a relatively low hypoconid and cristid obliqua. Given its early occurrence and primitive anatomy, Baataromomys may eventually help to clarify the phylogenetic relationships among basalomomyids, but more complete specimens will be required to test this possibility. Baataromomys brandti from the basal Wasatchian zone Wa-0 in the northern Bighorn Basin, Wyoming, was previously allocated to Teilhardina. However, several dental features shared by B. brandti and B. ulaanus suggest that they are closely related. The co-occurrence of Baataromomys in Asia and North America indicates that small-bodied euprimates were able to dispersal across the Beringian region near the Paleocene-Eocene boundary.